Relationship between Premature Rupture of Membranes and Collagen Amount in Chorioamnionic Membranes in Term Pregnancy (Global Journal of Medical Research, 2014)
Abstract not found
Keywords: electron microscopy; premature rupture of membranes; pregnancy